PRODUCTION OF BIOPLASTIC AND THEIR APPLICATIONS AS FOOD PACKAGING: PLA AND PHB - Chico, Mayra Fernanda (2022)
Food industry contributes around 40% of the containers and packaging used and discarded until 2020 worldwide. Social, environmental and political interest towards the development of biodegradable containers is growing, as is the demand of consumers for fresh and quality food products. Bioplastics are classified according to their chemical composition, origin and synthesis process. Polyhydroxyalkanoates (PHA) are materials of microbial origin, while polylactic acid (PLA) is obtained from lactic acid and the chemical reaction of lactide that produces the biomaterial. This work explores, through a bibliographic review, the principles and production of bioplastics made from polylactic acid (PLA) and polyhydroxybutyrate (PHB) and their application in food packaging. These materials constitute particularly interesting materials due to their potential in a wide range of applications. Physical-chemical properties of the biomaterials requested to make food packaging are: permeability to moisture, oxygen permeability and mechanical properties. The requirements established for the different types of packaging used in the food industry can be achieved by these biomaterials. In the same way, the environmental, economic and industrial advantages and the challenges encountered for their massive use have been estimated. It was identified that the reduction of manufacturing costs can be achieved through the use of agricultural biomass residues as a source of substrate for fermentation processes. PLA and PHB are particularly interesting materials due to their potential in a wide range of applications in the food industry due to their biodegradation capacity and efficiency.